2003
DOI: 10.1124/jpet.102.041533
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammatory Role of Prostaglandins during Experimental Meningitis: Evidence Suggestive of an in Vivo Relationship between Nitric Oxide and Prostaglandins

Abstract: Nitric oxide (NO) and prostaglandins are inflammatory mediators produced during meningitis. The purpose of the present study was to pharmacologically inhibit cyclooxygenase-2 (COX-2) and inducible NO synthase (iNOS) to 1) explore the prostaglandin contribution to blood-cerebrospinal fluid barrier permeability alterations and 2) elucidate the in vivo concentration relationship between prostaglandin E 2 (PGE 2 ) and NO during experimental meningitis. Intracisternal injection of lipopolysaccharides (LPSs, 200 g) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…53). NOS2 induction, and the subsequent generation of NO, in particular, were argued to contribute to pathology in S. pneumoniae BM (55,87). We found that induction of mRNA for NOS2, but not COX2, was strongly diminished in infected IFN-g gene-deficient animals at both 48 and 72 h p.i.…”
Section: Discussionmentioning
confidence: 58%
“…53). NOS2 induction, and the subsequent generation of NO, in particular, were argued to contribute to pathology in S. pneumoniae BM (55,87). We found that induction of mRNA for NOS2, but not COX2, was strongly diminished in infected IFN-g gene-deficient animals at both 48 and 72 h p.i.…”
Section: Discussionmentioning
confidence: 58%
“…In brain as in other organs, COX-2 is markedly upregulated in pathologies associated with inflammation and contributes to cytotoxicity both in vitro and in vivo 30,47,48 (see Hurley and colleagues 13 for a review). Although in the neurotoxicity associated with activation of NMDA receptors COX-2-derived prostanoids rather then radicals play a major role, it is unknown whether this is also the case in inflammation.…”
Section: Fig 1 Time Course Of Cox-2 Mrna Expression After Neocorticamentioning
confidence: 97%
“…Amongst the three isoforms of NOS, iNOS shows the highest activity. In fact, overproduction of NO by iNOS is implicated in a number of pathogenic conditions [27] including CDDP-induced degeneration of the SV [28]. Thus, we have examined expression of iNOS in the SV following CDDP treatment.…”
Section: Reactive Radical Species In Damage Of Marginal Cellsmentioning
confidence: 99%